2008
DOI: 10.1213/ane.0b013e318165df18
|View full text |Cite
|
Sign up to set email alerts
|

Less Impairment of Hemostasis and Reduced Blood Loss in Pigs After Resuscitation from Hemorrhagic Shock Using the Small-Volume Concept with Hypertonic Saline/Hydroxyethyl Starch as Compared to Administration of 4% Gelatin or 6% Hydroxyethyl Starch Solution

Abstract: Resuscitation from hemorrhagic shock with HS-HES 200/0.62 results in less impairment of clot formation when compared with compensation of blood loss by administering 6% HES 130/0.4 or 4% gelatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
2
26
0
3
Order By: Relevance
“…[30][31][32] Starches have also been shown to affect measurement of plasma fibrinogen concentration with the Clauss method. 33 Therefore, the use of HES 130/0.4 in our population may have contributed to the lower MCF cut-off value.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Starches have also been shown to affect measurement of plasma fibrinogen concentration with the Clauss method. 33 Therefore, the use of HES 130/0.4 in our population may have contributed to the lower MCF cut-off value.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro and in vivo studies have reported an anticoagulant effect or impaired platelet function after the use of hyperosmolar solutions, whereas new animal studies found less impairment of the plasmatic coagulation system compared with HES and gelatin 24 .…”
Section: Dilutional Coagulopathymentioning
confidence: 99%
“…Dies wird in den aktuellen BÄKEmpfehlungen expli zit betont [13]. Der Einfluss von 4 ml/kg KG hypertoner/hyperonkotischer HAES Lösung auf die Gerinnselbildung war in einer thrombelastometrischen Studie mit Schweinen deutlich geringer als der von 6% HAES 130/0,4 oder 4%iger Gelatine lösung [31]. Um ein ausreichendes Sau erstoffangebot im Gewebe zu erreichen, sind die Zielwerte der Volumensubstitu tion ein mittlerer arterieller Druck ("me an arterial pressure", MAP) von ≥65 mm Hg bzw.…”
Section: Permissive Hypotensionunclassified